Predictors of Male Involvement in Postnatal Care in Jambi, Indonesia: A Cross-Sectional Study - Guspianto, G.; Ibnu, I. N.; Veruswati, M.; Asyary, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Postpartum care (postnatal care, or PNC) is crucial for the health of mothers and newborns. After child delivery, mothers and babies should have optimal access to the health care system to utilize the facilities and skilled health workers. The involvement of men has a positive impact on the use of PNC and plays an important role in reducing delays, especially in preventing maternal and newborn deaths. Objectives. This study assessed the level of the involvement of men in PNC and analyzed the factors that determined this involvement. Methods. A cross-sectional study was conducted through a survey of 381 males who were selected by multistage random sampling in Muaro Jambi, Indonesia, from April to August 2020. The dependent variable was the involvement of men in PNC, which was constructed from four dichotomous indicators. Multiple logistic regression analysis was performed using SPSS 24.0 at a significance level of 0.05. Results. Over 50% of respondents were highly involved in PNC, with the predicting factors being the number of children (OR = 2.195, 95% CI = 1.096-4.397), the quality of health service (OR = 6.072, 95% CI = 3.324-11.09), communication (OR = 6.908, 95% CI = 3.255-14.66), and culture (OR = 4.031, 95% CI = 2.196-7.399). The communication factor was the main predictor of male involvement in PNC in Muaro Jambi Regency. Conclusion. The involvement of men in PNC in Muaro Jambi Regency was related to the number of children, quality of health service, communication, and culture. Counseling “as a couple” is needed to improve the communication between husband and wife so that they can understand each other’s needs in PNC.